EUCHARIST AND SPIRITUALITY IN LIBERATION THEOLOGY WITH SPECIAL REFERENCE TO GEORGE M. SOARES-PRABHU AND ITS IMPLICATIONS FOR A NEW WORLD ORDER - George, Oommen (Asian Horizons, 2011)
Eucharist is the source and summit of Christian life. Eucharist is the formula for the redemption of the humankind and of the entire cosmos since it focuses on a new world order founded on justice, peace, love and integrity of creation. It is a symbol, a commemoration and a participation in Jesus’ Liberative action and hence it is dynamic and revolutionary.